Blastocystis Colonization Alters the Gut Microbiome and, in Some Cases, Promotes Faster Recovery From Induced Colitis - Billy, Vincent; Lhotská, Zuzana; Jirků, Milan; Kadlecová, Oldřiška; Frgelecová, Lucia; Parfrey, Laura Wegener; Pomajbíková, Kateřina Jirků (Frontiers in Microbiology, 2021)
Protists are a normal component of mammalian intestinal ecosystems that live alongside, and interact with, bacterial microbiota. Blastocystis, one of the most common intestinal eukaryotes, is reported as a pathogen that causes inflammation and disease, though health consequences likely vary depending on host health, the gut ecosystem, and genetic diversity. Accumulating evidence suggests that Blastocystis is by and large commensal. Blastocystis is more common in healthy individuals than those with immune mediated diseases such as Inflammatory Bowel Diseases (IBD). Blastocystis presence is also associated with altered composition and higher richness of the bacterial gut microbiota. It is not clear whether Blastocystis directly promotes a healthy gut and microbiome or is more likely to colonize and persist in a healthy gut environment. We test this hypothesis by measuring the effect of Blastocystis ST3 colonization on the health and microbiota in a rat experimental model of intestinal inflammation using the haptenizing agent Dinitrobenzene Sulfonic acid (DNBS). We experimentally colonized rats with Blastocystis ST3 obtained from a healthy, asymptomatic human donor and then induced colitis after three weeks (short term exposure experiment) or after 13 weeks (long term exposure experiment) and compared these colonized rats to a colitis-only control group. Across experiments Blastocystis ST3 colonization alters microbiome composition, but not richness, and induces only mild gut inflammation but no clinical symptoms. Our results showed no effect of short-term exposure to Blastocystis ST3 on gut inflammation following colitis induction. In contrast, long-term Blastocystis exposure appears to promote a faster recovery from colitis. There was a significant reduction in inflammatory markers, pathology two days after colitis induction in the colonized group, and clinical scores also improved in this group. Blastocystis colonization resulted in a significant reduction in tumor necrosis factor alpha (TNFα) and IL-1𝛽 relative gene expression, while expression of IFNg and 17re/IL17C were elevated. We obtained similar results in a previous pilot study. We further found that bacterial richness rebounded in rats colonized by Blastocystis ST3. These results suggest that Blastocystis sp. may alter the gut ecosystem in a protective manner and promote faster recovery from disturbance.